Gastroduodenal Intussusception in Peutz-Jeghers Syndrome. Issue 1 (19th January 2022) - Mokhtari, Ayoub; De Leucio, Alessandro; Boitsios, Grammatina
Teaching points : Gastroduodenal intussusception is an infrequent cause of abdominal pain in children, for which a lead-point is nearly ubiquitous, which imposes endoscopic reduction as the first line of treatment.